2007
DOI: 10.1128/aem.01251-06
|View full text |Cite
|
Sign up to set email alerts
|

Detection of UV-Induced Thymine Dimers in IndividualCryptosporidium parvumandCryptosporidium hominisOocysts by Immunofluorescence Microscopy

Abstract: To investigate the effect of UV light on Cryptosporidium parvum and Cryptosporidium hominis oocysts in vitro, we exposed intact oocysts to 4-, 10-, 20-, and 40-mJ ⅐ cm ؊2 doses of UV irradiation. Thymine dimers were detected by immunofluorescence microscopy using a monoclonal antibody against cyclobutyl thymine dimers (anti-TDmAb). Dimer-specific fluorescence within sporozoite nuclei was confirmed by colocalization with the nuclear fluorogen 4,6-diamidino-2-phenylindole (DAPI). Oocyst walls were visualized usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 24 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…Moreover, monoclonal antibodies against cyclobutane thymine dimers are used in immunofluorescence microscopy for the detection of photorepair (Roza et al 1991;Al-Adhami et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, monoclonal antibodies against cyclobutane thymine dimers are used in immunofluorescence microscopy for the detection of photorepair (Roza et al 1991;Al-Adhami et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…As to other possible cellular defense mechanisms, researchers have investigated UV-induced DNA damage in C. parvum oocysts, but no evidence was found that DNA repair would be capable of restoring oocyst infectivity (2,20,21,23).…”
Section: Discussionmentioning
confidence: 99%
“…A batch of 3 ϫ 10 6 oocysts was subjected to MOS at a 25-mg/liter FAC concentration for 1 h. The oxidant was quenched, and the oocysts were briefly centrifuged and resuspended in distilled water. The oocyst suspension was incubated at 22°C, during which aliquots of 10 5 oocysts were taken at different time intervals (1,2,4,6,8,12,16, and 24 h), and a second heat shock was applied at the 24-hour time point to measure the extent of the oocysts' heat shock response during a 4-h interval, using the qRT-PCR amplification of the Hsp70 mRNA. The controls were (i) the same number of oocysts subjected initially to heat shock at 45°C for 20 min but not treated with chlorine oxidants and also (ii) oocysts completely killed by exposure to 65°C for 1 h in 10% ammonia.…”
Section: Stress Response Induced By Chlorine-based Oxidants Inmentioning
confidence: 99%
“…This may be related to the well-established mechanism of UV disinfection, i.e. bactericidal and bacteriostatic effect of UV mainly through genetic damages induction (Gaid et al 2006, Al-Adhami et al 2007). This effect of UV irradiation can be potentialized by other pretreatments decreasing BDOC like ozonation/GAC adsorption since dissolved organic matters are necessary to repair cell damages (Alkan et al 2007, Camper 2004.…”
Section: Discussionmentioning
confidence: 99%